2020
DOI: 10.1002/ejic.202000115
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Light‐Activated Spin Crossover in Iron(III) qnal Complexes

Abstract: Three iron(III) complexes, [Fe(qnal) 2 ]Y {qnal = 1-[(8-quinolinylimino)methyl]-2-naphthalenolate; Y = NO 3 1, BPh 4 ·CH 2 Cl 2 2, NCS 3} have been prepared to explore anion effects in spin crossover systems. Structural studies on 2 reveal supramolecular chains formed by π-π and C-H···π interactions between the [Fe(qnal) 2 ] + cations. Magnetic susceptibility measurements show the onset of spin crossover in 1 above 200 K, [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
(86 reference statements)
2
8
0
Order By: Relevance
“…Both L 2 (720 eV) and L 3 (707 eV) edges shift to higher binding energy with decreasing temperature from 340 K to 120 K, which confirms the HS to LS transition of the molecule occurs at lower temperature in the powder form (see Fig. S3B† for T dependent magnetic hysteresis loop) as compared to that of the molecule on the graphene surface in agreement with a previously reported transition of the SCO molecule in powder form where the transition temperature T 1/2 for cooling is 248 K and T 1/2 for heating is 278 K. 26,39…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Both L 2 (720 eV) and L 3 (707 eV) edges shift to higher binding energy with decreasing temperature from 340 K to 120 K, which confirms the HS to LS transition of the molecule occurs at lower temperature in the powder form (see Fig. S3B† for T dependent magnetic hysteresis loop) as compared to that of the molecule on the graphene surface in agreement with a previously reported transition of the SCO molecule in powder form where the transition temperature T 1/2 for cooling is 248 K and T 1/2 for heating is 278 K. 26,39…”
Section: Resultssupporting
confidence: 89%
“…Both L 2 (720 eV) and L 3 (707 eV) edges shift to higher binding energy with decreasing temperature from 340 K to 120 K, which confirms the HS to LS transition of the molecule occurs at lower temperature in the powder form (see Fig. S3B for T dependent magnetic hysteresis loop) as compared to that of the molecule on the graphene surface in agreement with a previous report Please do not adjust margins Please do not adjust margins the transition of the SCO molecule in powder form where the transition temperature T ½ for cooling is 248 K and T ½ for heating is 278 K. 26,39 To further confirm the spin transition of the monolayers on graphene, we recorded the X-ray magnetic circular dichroism (XMCD) spectra in total electron yield mode with a magnetic field applied to the sample, which is parallel to the circularly polarized photoelectron propagation vector. All the spectra are reported with a magnetic field of ±1.5 T at different temperatures.…”
Section: Please Do Not Adjust Marginssupporting
confidence: 90%
“…The LIESST effect has been observed in many SCO compounds; however, the reverse-LIESST effect that the HS species is photoexcited to the metastable LS state has been relatively less investigated. , We tried to study the reverse-LIESST effect on the three HS compounds 1 , 4 ·MeOH, and 4 , and found that compound 4 ·MeOH did show a reverse-LIESST effect upon exposure to a 1064 nm laser (13 mW·cm –2 , Figure S20a, Supporting Information). Taking into account the photothermal effect of near-infrared light on the reverse-LIESST effect, the χ M T values were recorded under light irradiation for approximately 2160 min (Figure S20b, Supporting Information), which showed a slow decrease from 4.52 to 3.40 cm 3 K mol –1 and remained invariant after the light was switched off, demonstrating that the photothermal effect could be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…These data show the occurrence of SCO in the Fe1 center is accompanied by a larger structural distortion of the coordination sphere. The capability of compounds 2 and 3 to present reversible LIESST effects may be attributed to variable coordination-sphere environments of Fe­(III) ions upon spin-state changes because large changes in the distortion parameters and the Fe-ligand bond distances during HS ⇌ LS transition have been suggested to favor the occurrence of the LIESST effect. ,,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation